Enlisting healthcare professionals in the campaign against incendiary weapons. Issue 2 (March 2022) - Docherty, Bonnie; Schneider, Jeffrey C.
Abstract: AThe exceptionally severe burns caused by incendiary weapons make strengthening international law a humanitarian imperative. Given healthcare professionals' deep understanding of the human cost of burn injuries, they are in a unique position to urge governments to initiate a process to assess the law's shortcomings at a major UN disarmament meeting in December. One way to advocate for such policy change is by signing an open letter from healthcare professionals and burn survivor organizations.